ANALISIS DETERMINAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SUMBAWA - Elly Karmeli; Wahyu Haryadi; Indah Ade Puji Astuti (Jurnal Ekonomi & Bisnis, 2020)
The purpose of this study was to know the effect of regional taxes, retribution, the results of separated regional wealth management and other legitimate local revenue toward the realization of own source revenue (PAD) of Sumbawa Regency in 2012-2018. The method used was multiple linear regression test, t-test, f-test and coefficient of determination (R2). The conclusion of study stated that the independent variables, namely local taxes, local levies, the results of separated regional wealth management and other legal local revenue were able to explain the realization of own source revenue of 1000 or 100%, if seen from the f test on the ANOVAb table simultaneously, the independent variable did not had effect and was significant toward original regional income because the value of F-value was lower than F-table or (1.423<19.25) with the Sig. 000. While partially only regional taxes and the results of regional wealth management were separated which had a significant effect, meanwhile, the other two variables, namely regional retribution and others, had less significant effect toward the regional original income of Sumbawa.